(untitled) (British Journal of Global Ecology and Sustainable Development, 2023)
This article is written about the role of student activity in the educational process of digitization, the data system, the Hemis program and the system of credit modules. The article shows the specific significance and role of digitalization in the educational process of students. The article, written on the basis of scientific research, promising scientific considerations and practical experience related to this topic, also outlines the Hemis program and the system of credit modules.